The use of the micro-computed tomography in age estimation (Research, Society and Development, 2022)
Age estimation is important in Forensic Anthropology because it allows estimating the age of individuals, in addition to performing a significant role in legal proceedings. Teeth as well as the human skeletal measures are reliable structures during the identification process. Micro-computed tomography (micro-CT) is a non-destructive 3D technology to allow the visualization and analysis of microstructural of bones and teeth. The aim of this study was to analyze, through a literature review, the age estimation using micro-CT. For this purpose, articles published in the last 20 years and made available in full in Portuguese, English and Spanish were used. Micro-CT is considérate a reliable alternative for age estimation through measurements on human teeth and skeletons. The association of this tool with other techniques provides promising results, besides to proposing new methods through quantitative análisis in high-resolution.